Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas X SMA Negeri 1 Pagaran Tahun Pembelajaran 2022/2023 - Pebriana Harianja; Andar Gunawan Pasaribu; Johari Manik; Meditatio Situmorang; Risden Anakampun (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The aim of this research is to determine the positive and significant influence of the Problem Based Learning (PBL) learning model on the learning motivation of Christian Religious Education and Character in Class X SMA Negeri 1 Pagaran for the 2022/2023 Academic Year. The method used in this research is descriptive quantitative. The population is all classes Data was collected using a positive closed questionnaire totaling 36 items, of which 15 questionnaire items were for variables Christianity and Characteristics of Class Thus it is known that there is a positive relationship between variables b) Regression coefficient of determination test (r2) = 24.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=15, dk denominator=n-2=42-2=40) namely 12.83 > 1.92. Thus Ha is accepted and H0 is rejected where F calculated is greater than F table, then there is a positive and significant influence between the Problem Based Learning (PBL) learning model on the learning motivation of Christian Religious Education and Character of Class X SMA Negeri 1 Pagaran in the Learning Year 2022/2023 amounting to 24.3%.